Do desenvolvimentismo ao alinhamento à conduta militar: as peripécias da política campinense (1963-69). - Marques, Thiago Trindade (2012)
This research is related to the city of Campina Grande PB, highlight a uniqueness of the public policies in use in the city which is considered a leading city in the region. We find in the boiling of the politics of the 60 s, the ideal timing to measure the power of the city. At that time the so-called Queen of Borborema headed some measures to make its industrialization possible, building the myth of leading vocation the city has in inland of the northeast region. The administration of Williams Arruda is seen as the main period of the development projects during all the political and socialagitation resulting from the coup d'etat against the Brazilian Democratic Institutions in 1964. Moreover, the impact of the developmental measures in the economy of the city, considering the changes in access to the public services in the city, such as the changes in the educational area, in which the main objective was to stimulate the qualified, working force for the factories to come at that time. For the research we used data published by IBGE, results released by TRE-PB, news sources from that time as well as existing academic work on the subject to bring out the debate. The research satisfies the line of research Regional History , focusing the discussion of the political history of Campina Grande, and in the possibilities to contextualization with the national sociopolitical context.